اردو نعت کی شعری روایت میں سیرت پاکؐ کی عکاسی - Kamal, Prof. Dr. Muhammad Ashraf (Zoraiz, 2022)
Character is called the path and appearance and it refers to the habits and manners of any person. Every person has some kind of character and temperament. The biographies of the great and great people are more important and worthy of imitation than the common man. Due to the qualities of the high biographies of the great and great people, a whole field of biographies has emerged. Biography should be such that the embodiment of moral virtues comes out. And biography should be described in such simple words that it is easy to understand and follow. It is related to his existence and all the things in which his life and events and his habits and characteristics from the birth of the Holy Prophet to his death are described, that is the biography is applied. In this article the biographical aspects of the Holy Prophet are mentioned through Urdu Naat. These elements of Naat are a great source of observing manners and ethical values.